A study on the efficacy of AFO stiffness prescriptions. (2nd January 2021) - Vasiliauskaite, Egle; Ielapi, Alessio; De Beule, Matthieu; Van Paepegem, Wim; Deckers, Jan Patrick; Vermandel, Miguel; Forward, Malcolm; Plasschaert, Frank
Abstract: Purpose: Ankle foot orthosis (AFO) stiffness is a key characteristic that determines how much support or restraint an AFO can provide. Thus, the goal of the current study is twofold: (1) to quantify AFO prescriptions for a group of patients; (2) to evaluate what impact these AFO have on the push-off phase. Method: Six patients were included in the study. Three patients were prescribed an AFO for ankle support and three patients were prescribed an AFO for ankle and knee support. Two types of AFO – a traditional polypropylene AFO (AFOPP) and a novel carbon-selective laser sintered polyamide AFO (AFOPA), were produced for each patient. AFO ankle stiffness was measured in a dedicated test rig. Gait analysis was performed under shod and orthotic conditions. Results: Patient mass normalized AFOPP stiffness for ankle support ranged from 0.042 to 0.069 N·m·deg −1 ·kg −1, while for ankle and knee support it ranged from 0.081 to 0.127 N·m·deg −1 ·kg −1 . On the group level, the ankle range of motion and mean ankle velocity in the push-off phase significantly decreased in both orthotic conditions, while peak ankle push-off power decreased non-significantly. Accordingly, on the group level, no significant improvements in walking speed were observed. However, after patient differentiation into good and bad responders it was found that in good responders peak ankle push-off power tended to be preserved and walking speed tended to increase. Conclusions: Quantification of AFO stiffness may help to understand why certain orthotic interventions are successful (unsuccessful) and ultimately lead to better AFO prescriptions. Implications for rehabilitation: AFO ankle stiffness is key characteristic that determines how much support or restraint an AFO can provide. In a typical clinical setting, AFO ankle stiffness is not quantified. AFO has to meet individual patient's biomechanical needs. More objective AFO prescription and more controlled AFO production methods are needed to increase AFO success rate.